Electron detachment and subsequent structural changes of water clusters - Das, Susanta; Sengupta, Turbasu; Dutta, Achintya Kumar; Pal, Sourav (Journal of Physical Chemistry A, 2016)
A cost-effective equation of motion coupled cluster method, EOMIP-CCSD(2), is used to investigate vertical and adiabatic ionization potential as well as ionization-induced structural changes of water clusters and compared with CCSD(T), CASPT2, and MP2 methods. The moderate N-5 scaling and low storage requirement yields EOMIP-CCSD (2) calculation feasible even for reasonably large molecules and clusters with accuracy comparable to CCSD(T) method at much cheaper computational cost. Our calculations shed light on the authenticity of EOMIP-CCSD(2) results and establish a reliable method to study of ionization energy of molecular clusters. We have further investigated the performance of several classes of DFT functionals for ionization energies of water clusters to benchmark the results and to get a reliable functionals for the same.